Hydrothermal synthesis, characterization, and visible light-driven photocatalytic properties of Bi2WO6 nanoplates - Phuruangrat A. (Hindawi Publishing Corporation, 2014)
In this research, the effects on reaction temperature and length of time on Bi2WO6 nanoplates by hydrothermal synthesis on morphologies and photocatalytic properties were studied. The products obtained at different reaction temperature and reaction time were characterized by XRD, Raman, FTIR, SEM, and TEM techniques. The photocatalytic properties of the samples were measured by decomposing the rhodamine-B organic dye. XRD pattern was specified as pure orthorhombic well-crystallized Bi2WO 6 phase for the 180°C and 20 h synthesis. Its FTIR spectrum shows main absorption bands at 400-1000 cm-1, assigned to Bi-O stretching, W-O stretching, and W-O-W bridging stretching modes. SEM and TEM analyses show that the product was composed of nanoplates. Photocatalytic activity of Bi 2WO6 nanoplates shows the 98.24% degradation of rhodamine-B under the Xe light irradiation within 100 min. © 2014 Anukorn Phuruangrat et al.